Modulation of pTau181 by Glypican-1-Derived Heparan Sulfate in Human Neural Progenitor Cells and ApoE4-Expressing Induced Neurons - Cheng, Fang; Fransson, Lars Åke; Mani, Katrin ; 0000-0002-1821-0634 (Journal of Neurochemistry, 2025)
In Alzheimer's disease (AD) there is accumulation of amyloid-β (Aβ) and hyperphosphorylated tau (pTau) in the brain. Aβ activates kinases that phosphorylate tau. Increased pTau181 is a signal for hyperphosphorylation of tau. The generation of Aβ from amyloid precursor protein (APP) and the release of heparan sulfate (HS) from the proteoglycan glypican-1 (GPC1) are interconnected. Release of HS is APP-, ascorbate-, copper-, and NO-dependent. HS-Aβ interactions may regulate tau phosphorylation in human neural stem cells (NSC). The most influential risk factor for sporadic AD is the presence of the ε4 allele of apolipoprotein E (ApoE). Here, we have further explored the interplay between GPC1-derived HS and pTau181 formation in human neural progenitor cells (NPC) and induced neurons (iN) obtained by reprogramming of human fibroblasts from ApoE3- and ApoE4-carriers. HS release from GPC1 was either suppressed or stimulated, and effects on pTau181 were monitored by immunofluorescence microscopy and quantified by intensity measurements as well as by enzyme-linked immunosorbent assay (ELISA) technique. Stimulation of HS release decreased pTau181 in NSC but was without effect in NPC, where tau was mostly in the nuclei. However, suppression of HS release in NPC increased pTau181. Stimulation of HS release decreased pTau181 in ApoE4/4-iN but not in ApoE3/3-iN. A high intake of vitamin C may be of prophylactic value in ApoE4-positive individuals. (Figure presented.)
Keywords: Alzheimer's disease; amyloid beta; heparan sulfate; phosphorylation; tau; vitamin C